Orientasi Strategy pada Industri Fashion Tradisional - Rainier Hendrik Sitaniapessy (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of learning orientation, technology orientation, and entrepreneurial orientation on the marketing performance of Ambon traditional clothing products. The study used a quantitative approach with an explanatory survey design. Primary data were collected by distributing structured questionnaires to 100 customers of Ambon traditional clothing products in Ambon City who were selected using a purposive sampling technique based on their experience of purchasing and using the products. The data obtained were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) through the stages of testing the measurement model (outer model) and structural model (inner model) to test the validity, reliability, and relationships between research variables. The results showed that learning orientation, technology orientation, and entrepreneurial orientation had a positive and significant effect on marketing performance. Among the three variables, entrepreneurial orientation had the most dominant influence in improving the marketing performance of Ambon traditional clothing products. These findings indicate that the ability of business actors to develop organizational learning, utilize digital technology, and create entrepreneurial innovation is an important factor in strengthening competitiveness and increasing the effectiveness of marketing local cultural products in the digital era.